Superior strength-ductility synergy in a novel tailored nanoparticles-strengthened medium-entropy alloy. (15th January 2022) - Peng, Hanlin; Baker, Ian; Hu, Ling; Li, Liejun
Abstracts: A novel f.c.c. (CoCrNi)94 Al3 Ti3 medium-entropy alloy strengthened with an L12 phase was designed using CALPHAD. Hot rolling, cold rolling, and heat treatment were used to produce a fine grain size (0.61 μm) and a high volume fraction (0.37) of coherent 23.2 nm diameter L12 nanoparticles. This tailored microstructure exhibited an excellent strength-ductility synergy (yield stress∼1203 MPa, ultimate tensile strength∼1577 MPa, elongation ∼24%) and a high working hardening rate (3700 MPa at strain of 5%). The contributions from grain boundary strengthening and precipitation strengthening to the yield strength were estimated to be ∼61%. After the tensile tests, the fraction of LAGBs sharply increased and that of Σ3 n coincidence site lattice boundaries decreased: inverse pole figures indicate the formation of a {101}<111> texture. Such an ultrafine grain size suppressed deformation twinning, while applied stress led to a higher density of geometrically-necessary dislocations at the grain boundaries compared to the grain interiors. Graphical abstract: Image, graphical abstract